(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Introduction: COVID-19 was a new SARS variance identified in 2019 and declared the cause of the global pandemic in March 2020. Nowadays, the case has experienced a fluctuating case phase, along with the mutation of the SARS Cov-19 variant that has not stopped yet. Confirmation cases and deaths occur in various ages, including in children. Although the data on COVID-19 case in children is low, efforts to prevent the transmission of Covid-19 in children is needed.Objective: This study aims to identify the effect of health education efforts to prevent Covid-19 transmission through 3M (wearing a mask, washing hands and physical distancing) habituation which was carried out using comic media with a cultural context.Method: This study uses pre-experimental research with one group pretest-posttest design. The study was conducted to see the effect of providing education using culture-based comic media (independent variable) on elementary school students' attitudes in 3M practice (dependent variable). The population in this study were all students aged 10-12 years at MI Al-Kautsar Sorong, a total of 45 children. In this study, the sampling technique used is total sampling. The data were analysed with the Wilcoxon test.Result: The mean score post-test was significantly higher than the pre-test (pre-test 70,67; post-test 74,71; p-value 0,01). The difference score pre-test and post-test in categorical scoring showed significant differences; in the post-test group, as much as 46,67% (21 children) scored is good. Students' characteristic related to the post-test scores is age (p-value 0,001); the older children, the higher score they got.Conclusion: Comics with cultural context media can be considered alternative health promotion media for children.